2019
DOI: 10.1002/stem.2965
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic Changes Underline Plasticity of Murine Embryonic Stem Cells

Abstract: Murine embryonic stem cells (mESCs) are endowed by a time-dependent window of plasticity during their early commitment steps. Indeed, while mESCs deprived of leukemia inhibitory factor (LIF) for 24 hours revert to their naive pluripotent state after subsequent LIF readdition, cells deprived of LIF for 48 hours are no longer efficient in reverting, upon LIF addition, and undergo irreversible differentiation. We investigated undisclosed bioenergetic profiles of early mESCderived committed cells versus their undi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Apoptosis was detected with an Annexin V-FITC kit (Beckman Coulter, Carlsbad, CA, USA) according to the manufacturer's protocol. Briefly, 10 5 cells from each of the experimental conditions were stained with Annexin V-FITC solution (AnnV) and propidium iodide (PI, 250 µg/mL) for 15 min at 4 • C in the dark, washed in phosphate buffer saline (PBS), and analyzed with a flow cytometer (BD Bioscience, FACS Canto II) (17). This technique allow to detect: unlabelled viable cell subpopulation (AnnV − / PI − ); early apoptotic cell subpopulation that have bound only AnnV (Ann + /PI − ); necrotic cell subpopulation (representing the cells in post-apoptosis necrosis or late apoptosis) that have both bound AnnV and have been labeled with PI (Ann + /PI + ).…”
Section: Apoptosis Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis was detected with an Annexin V-FITC kit (Beckman Coulter, Carlsbad, CA, USA) according to the manufacturer's protocol. Briefly, 10 5 cells from each of the experimental conditions were stained with Annexin V-FITC solution (AnnV) and propidium iodide (PI, 250 µg/mL) for 15 min at 4 • C in the dark, washed in phosphate buffer saline (PBS), and analyzed with a flow cytometer (BD Bioscience, FACS Canto II) (17). This technique allow to detect: unlabelled viable cell subpopulation (AnnV − / PI − ); early apoptotic cell subpopulation that have bound only AnnV (Ann + /PI − ); necrotic cell subpopulation (representing the cells in post-apoptosis necrosis or late apoptosis) that have both bound AnnV and have been labeled with PI (Ann + /PI + ).…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…Cells were then fixed with 900 µl of 70% cold ethanol (added dropwise), and incubated for 1 h at 4 • C. Cells were washed and resuspended in PBS with 0.2 mg/mL of bovine RNase A and incubated for 1 h at 37 • C in the dark. PI (10 µg/mL) was added, and the analysis was performed using flow cytometry (Bioscience, FACS Canto II) (17). The percentage of cells in each of the different cell cycle phases (G0/G1, S, and G2/M) was calculated from the linear graph on which cell counts were plotted relative to cell DNA content.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since mitochondrial enzymes of ETC are one of the main sources of intracellular ROS, highlighting the peculiarities of PSC energy metabolism led to the concept that the redox homeostasis in PSCs significantly differs from that of their differentiated progeny cells and that PSCs can limit intracellular ROS production to minimize ROS-induced oxidative damage. However, recent studies have shown that PSCs have not only phenotypic but also metabolic plasticity and, therefore, are able to adjust their redox metabolism to the conditions of their microenvironment [26,27]. These cells a priori have the capacity to exist not only in hypoxic conditions but also in normoxia (21% O 2 ) [26] and even hyperoxia (>21% O 2 ) [28].…”
Section: Introductionmentioning
confidence: 99%